The temple in early Christianity : experiencing the sacred - Regev, Eyal (New Haven ; London : Yale University Press, 2019)
"The first scholarly work to trace the Temple throughout the entire New Testament, this study examines Jewish and Christian attitudes toward the Temple in the first century and provides both Jews and Christians with a better understanding of their respective faiths and how they grow out of this ancient institution. The centrality of the Temple in New Testament writing reveals the authors' negotiations with the institutional and symbolic center of Judaism as they worked to form their own religion." -- Publisher description.
Introduction -- 1. Jesus: "Cleansing," trial, and Last Supper -- 2. Paul's letters: Temple imagery as religious identity -- 3. Mark: criticism or rejection? -- 4. Q and Matthew: the Sacred Temple -- 5. Luke-Acts: living and dying with the Temple -- 6. The Gospel of John: Temple and Christology -- 7. The Book of Revelation: the alternative Temple -- 8. Hebrews: the new heavenly temple cult based on the old one -- 9. Relating to Judaism, experiencing the sacred -- 10. Concluding thoughts.
Includes bibliographical references and indexes.
Eyal Regev is professor of Jewish studies in the department of Land of Israel studies and archaeology at Bar-Ilan University.
Print version record.
JSTOR
Keywords: Temple of Jerusalem (Jerusalem); Temple of Jerusalem (Jerusalem) -- In the Bible; Bible. -- Criticism, interpretation, etc; Temple de Jérusalem (Jérusalem); Bible. -- Critique, interprétation, etc; Temple of Jerusalem (Jerusalem); Bible; Christianity -- Early works to 1800.; RELIGION -- Biblical Studies -- Old Testament; RELIGION -- Judaism -- Sacred Writings; RELIGION -- Biblical Studies -- History & Culture; Temple of Jerusalem (Jerusalem) in the Bible; Christianity; Early works; Criticism, interpretation, etc